Math, asked by diyu68, 5 months ago

simplify :— (a²- b²)²​

Answers

Answered by Anonymous
8

Answer:

 {a}^{4}  - 2 {a}^{2}  {b}^{2}  +  {b}^{4}

Explanation :-

 ({a}^{2}  -  {b}^{2} ) ^{2}  \\  \\ using  \:  =  \\  \\ ( {a}^{2}  -  {b}^{2} ) {}^{2}   =  {a}^{2}  - 2ab +  {b}^{2}  \\  =  ({a}^{2} ) {}^{2}  - 2( {a}^{2} )( {b}^{2} )  + ( {b}^{2} ) {}^{2}  \\  \\  =  {a}^{4}  - 2  {a}^{2}  {b}^{2}  +  {b}^{4}

Step-by-step explanation:

_______________________

Here is your answer dear, hope it will helps you...

Have a great day ahead..

Similar questions